MANAJEMEN KEUANGAN, DIFERENSIASI PRODUK, DAN PEMASARAN BERBASIS DIGITAL SOLUSI NILAI TAMBAH PRODUK UMKM - Budiantoro, Harry; Suyana, Hilma; Hayurani, Herika; Destiyani, Annisa; Hestin, Hestin (Universitas Islam 45 Bekasi, 2025)
This community service program was conducted in Kadumaneuh Village with the objective of enhancing the quality of Micro, Small, and Medium Enterprises (MSMEs) engaged in the production of “kelomang” toys. These MSMEs face several critical challenges, including limited understanding of financial record-keeping, insufficient product innovation, and minimal utilization of digital media for marketing. Such conditions have constrained the competitiveness and market reach of “kelomang” products, ultimately leading to low turnover. The program employed three primary approaches. First, training sessions on basic financial record-keeping were provided to help MSME actors understand cash flow management, calculate profits, and manage business capital more effectively. Second, hands-on practice in product innovation focused on differentiating designs and diversifying materials to enhance product value and attract greater consumer interest. Third, mentoring on digital marketing strategies included the use of social media and e-commerce platforms to expand market reach, improve product visibility, and build a more professional brand image. The results demonstrated significant improvements in the partners’ ability to systematically manage their finances, develop more varied product innovations, and utilize digital platforms to extend their market presence. These achievements are expected to sustainably increase the competitiveness and turnover of MSMEs in Kadumaneuh Village, while also serving as a model for the development of creative enterprises based on local potential that are capable of competing in broader markets.